The Impacts of Public Administrative Quality on Profitable Enterprises in Vietnam - Bac Truong Cong; Doan Van Hoang (Borong Newinera Publisher, 2021)
This study aims to understand the relationship between the quality of public administration and the rate of profitable enterprises by locality in Vietnam in the period 2015 - 2019. With a combined data set from two sources including The first is the Provincial Competitiveness Index (PCI) dataset jointly implemented by the Vietnam Chamber of Commerce and Industry (VCCI) with the support of the United States Agency for International Development (USAID) in Vietnam, the second is the